Development of Interactive Powerpoint-Based English Learning Media for Grade XI Students MAN 1 East Lampung - Safitri, Lia; Suhono, Suhono; Pratiwi, Wiwied; Hidayah, Yayuk; Sari, Yeasy Agustina (Bulletin of Science Education, 2024)
This article aims to develop interactive powerpoint-based English learning media for grade XI students of MAN 1 East Lampung. This research method is research and development (R&D) with the ADDIE model. ADDIE research stages include analyze, design, development, implementation, and evaluation. This research instrument is an interview sheet, validation sheet, student and teacher response questionnaire. This research data analysis technique uses qualitative and quantitative descriptive techniques. Qualitative descriptive analysis was conducted on the results of interviews. Quantitative descriptive analysis was carried out on the results of expert validation and student and teacher response questionnaires. Based on the analysis conducted, the percentage of feasibility results from material experts was 92.5% with the criteria "very worthy", the validation results from language experts were 81.25% with the category "very worthy" and the validation results from media experts were 94.73% with the criteria "very worthy". And also evidenced by the results of the trial to students with a percentage of 85.108% with the criteria "very worthy" as well as a teacher response questionnaire which obtained a percentage of 96.66% with the category "very worthy". Based on the results of the data obtained, it shows that interactive powerpoint media is very worthy for use in the learning process. Keywords: Interactive Powerpoint, Learning Media, English Learning Media